Effects of ultrasonic energy on dyeing of polyamide (microfibre)/Lycra blends - (:unkn) unknown (ELSEVIER SCIENCE BV, 2004)
Although ultrasonic energy is widely used cleaning and degreasing of parts and assemblies in automotive and other industries, the use of ultrasonic energy in an industrial scale for textile washing is very new. This is due to the complexity of controlling the combination of chemical and mechanical effects, whereas with degreasing of machine parts only the mechanical effects is applied. The use of ultrasonic energy in dyeing PA/Lycra fabrics with reactive dyes has been studied spectrophotometrically in this work. PA/Lycra (85/15) blends have been dyed using conventional and ultrasonic dyeing techniques with three reactive dyes containing different chromophore and reactive groups. The dyeing carried out conventionally and by the use of ultrasonic techniques. The results were compared in terms of percentage exhaustion; total dye transferred to the washing bath after dyeing and the fastness properties. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: ultrasonic energy; ultrasonic dye; polyamide